International learning communities: What happens when leaders seek to learn across national boundaries? - Mehta, Jal; Peterson, Amelia (Journal of educational change, 2019)
The past decade has seen increasing international education activity and interest from policymakers and think tanks in looking to other countries for educational reform strategies. This “new isomorphism”—the notion of global best practices in education—has been the subject of intensive debate between advocates and critics. But missing from this debate is an empirical account of what actually happens when global leaders gather, whether these leaders accept or resist borrowing from abroad, and, more constructively, how such gatherings might be organized to promote productive learning. Given these gaps, our research examines the emergence of what we call International Learning Communities (ILCs), which are sustained efforts to support public education leaders in ongoing cross-national learning. In this paper, we describe the nature of these communities and re-evaluate their role in the new isomorphism. Drawing on observations of two such communities and interviews with 30 ILC participants, we conclude that this model offers three types of learning: borrowing, co-construction, and systems thinking. While we view each as useful, we suggest that systems thinking is critical if international lessons are going to be effectively assimilated into coherent, contextually-appropriate strategies. Our findings are relevant not only for the continued study and development of system-level international learning, but also for all who seek to learn from other nations’ educational policy and practice.